Estimating Germany's Potential Output - Gustav Horn; Camille Logeay; Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
Potential output measures a country's attainable aggregate living standard and is thus one of the most important categories of economics. It is also a key indicator for monetary and fiscal policy. Despite its prominence, however, potential output is a difficult concept to pinpoint both theoretically and even more so empirically. The article discusses the reasons for the marked revisions of potential output estimates by major international organisations. The authors then present the results of our attempts to quantify Germany's potential output based on a production function approach coupled with the Kalman-filter technique to estimate the NAIRU. The authors find that potential output and potential output growth greatly depend on how the NAIRU and potential total factor productivity are modelled. Given the difficulties involved in robustly estimating potential output, especially in real time, economic policy makers need to learn to pursue their policy objectives without reference to this variable.
urn:nbn:de:101:1-20080814203
Keywords: C5; E32; E52; O11; 330; Potential Output; Nairu; Kalman-filter; revisions